TEORI ALJABAR AL-KHWARIZMI BENTUK x^2+bx=c - Ahmad Isroil; Faiqotur Rohmah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The purpose of writing this article is to explain how al-Khwarizmi's theory of algebra. Al-Khwarizmi's algebraic theory introduces a geometrical algebraic approach. In the book fi al-jabr wa al-muqabala, al-Khwarizmi gives an initial definition of squares, roots, and numbers. Al-Khwarizmi made three main principles of algebra through this definition. One of the principles discussed in this article is that the square plus the root equals the number (x2 +bx = c).